Degraded DNA samples made informative by using superprimers. (December 2017) - Mautner, Martin E.; Caputo, Mariela; Corach, Daniel
Abstract: The use of long ssDNA polynucleotides in PCR of degraded DNA samples can discriminate Short Tandem Repeat (STR) genotypes otherwise missed by current commercial kits.